2016
DOI: 10.1177/1534735416681640
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Cytolytic Activity in Murine Natural Killer Cells and Inhibition of Tumor Growth by the Ethanol Fraction of Oyster Extract

Abstract: A reduced number and/or reduced activity of natural killer (NK) cells, which are important for defense against a variety of cancers and viral infections, occur under various stress conditions and in patients with various diseases. In this article, we report that the 30% to 50% ethanol precipitate of oyster extract (EPOE50) dose-dependently enhanced the activity of mouse spleen NK cells in vitro and in vivo. The activity of EPOE50 was eluted with a molecular weight of about 2000 by gel filtration and was inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The authors discovered that GTLP were able to increase NK cell toxicity against YAC-1 cells and activate macrophages [94]. Finally, one study using polysaccharides extracted from animal origin (oyster) resulted in stimulation of the activity of mouse spleen NK cells in vitro and in vivo [95]. In conclusion, polysaccharides have also a stimulating effect on NK cells and might be an additional source of compounds supporting cancer treatment.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…The authors discovered that GTLP were able to increase NK cell toxicity against YAC-1 cells and activate macrophages [94]. Finally, one study using polysaccharides extracted from animal origin (oyster) resulted in stimulation of the activity of mouse spleen NK cells in vitro and in vivo [95]. In conclusion, polysaccharides have also a stimulating effect on NK cells and might be an additional source of compounds supporting cancer treatment.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Moreover, our results demonstrated that AECs treatment significantly increased the proportion of CD3 ‐ CD161 + NK cells and CD3 + CD161 + NKT cells. Interestingly, Kaito Sakaguchi et al observed that the 30–50% ethanol precipitate of oyster extract (EPOE50) enhanced the activity of mouse spleen NK cells in vitro and in vivo and then inhibited tumor growth in a dose‐dependent manner (Sakaguchi et al., 2018 ). In summary, AECs treatment may regulate the balance of cellular immunity and the body's humoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their nutritional value, oysters have considerable potential in the functional food industry, exhibiting beneficial health effects. Previous studies have demonstrated that oyster extracts possessed numerous biological properties, such as antitumor (Sakaguchi et al., 2018 ), antimicrobial (Huang et al., 2019 ; Karthikeyan et al., 2014 ), antioxidant (Watanabe et al., 2012 ), and immunomodulatory effects (Cheng et al., 2013 ; Li et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] Total proteins were calculated by multiplying the organic nitrogen content by 6.25 using the Kjeldahl method. [30] 3 RESULTS AND DISCUSSION…”
Section: Methodsmentioning
confidence: 99%